2018
DOI: 10.1038/s41584-018-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids for the treatment of rheumatic diseases — where do we stand?

Abstract: As medical use of cannabis is increasingly legalized worldwide, a better understanding of the medical and hazardous effects of this drug is imperative. The pain associated with rheumatic diseases is considered a prevalent indication for medicinal cannabis in various countries. Thus far, preliminary clinical trials have explored the effects of cannabis on rheumatoid arthritis, osteoarthritis and fibromyalgia; preliminary evidence has also found an association between the cannabinoid system and other rheumatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 120 publications
0
39
0
2
Order By: Relevance
“…Cannabinoids are known to interact with the immune system at multiple points including CB1 and CB2 receptors, six vanilloid channels, peroxisome proliferator-activated receptors (PPAR's), serotonin, adenosine, histamine, glycine, sphingosine, dopamine and opioid receptors, three class A orphan G-protein coupled receptors (GPCR's), toll-like receptors, Tcells, B-cells, macrophages and regulatory cells, effects on sodium channels and several types of potassium and calcium channels, modulation of GABA signalling and inhibition of cyclooxygenase and lipoxygenase enzymes, bind directly to mitochondria and cannabinoid receptors also form heterodimers with opioid, adenosine, dopamine, GABA and other GPCR's and have myriad and major epigenetic effects [13][14][15][16][17][18][19][20][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids are known to interact with the immune system at multiple points including CB1 and CB2 receptors, six vanilloid channels, peroxisome proliferator-activated receptors (PPAR's), serotonin, adenosine, histamine, glycine, sphingosine, dopamine and opioid receptors, three class A orphan G-protein coupled receptors (GPCR's), toll-like receptors, Tcells, B-cells, macrophages and regulatory cells, effects on sodium channels and several types of potassium and calcium channels, modulation of GABA signalling and inhibition of cyclooxygenase and lipoxygenase enzymes, bind directly to mitochondria and cannabinoid receptors also form heterodimers with opioid, adenosine, dopamine, GABA and other GPCR's and have myriad and major epigenetic effects [13][14][15][16][17][18][19][20][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly the cannabis industry is known to have recently increased its activity significantly in USA following widespread relaxation of regulations pertaining to its use, and a 2018 study indicated that legalization was associated with an increase of more than 1,000,000 cannabis users and 500,000 cannabis-dependent people 11 . A large literature describes the immunosuppressive properties of several cannabinoids including Δ9tetrahydrocannabinol (THC), cannabidiol and cannabinol [12][13][14][15][16][17][18][19][20] . Cannabis users frequently inhale with deep breaths which are held for long period so that smoke can penetrate deeply into the lung 12,21 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…1, 2 Delta-9-tetrahydrocannabinol (THC), the principal psychoactive constituent of cannabis, powerfully modulates immune function in peripheral cells, 3 in part, through activating cannabinoid receptor 2 (CBR2). 1, 36 In vitro studies of cannabis exposure, which contains over 450 compounds, show that it modulates immune function, 7–9 changes cytokine production, 8, 10, 11 inhibits cell proliferation, 2 and induces apoptosis. 12, 13 However, little is known about the mechanisms of in vivo THC exposure on the transcriptomes of distinct types of peripheral blood mononuclear cells (PBMCs) in humans.…”
Section: Mainmentioning
confidence: 99%
“…Cannabinoid receptors are found in a variety of tissues throughout the bodyfrom neurons in the frontal cortex, to the gastrointestinal tract and immune cells as well. 9 According to the "entourage theory," the combination of THC and CBD creates a synergistic effect in which other phytocannabinoids possibly take part as well, suggesting that there could be a benefit in using cannabis rather than synthetic cannabinoids as analgesic or therapeutic agents. 10…”
Section: Cannabinoidsmentioning
confidence: 99%